1982
DOI: 10.7863/jum.1982.1.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The comet tail artifact.

Abstract: A description and explanation of an unexpected echographic appearance in a patient who had sustained an abdominal shotgun wound is presented. In the B-scans, a trail of dense continuous echoes, simulating a comet tail, is seen distal to each lead pellet. This comet tail appearance is shown to be a type of reverberation artifact. The effect of object size, shape, composition, and orientation on the appearance of this artifact is demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0
8

Year Published

1985
1985
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(101 citation statements)
references
References 1 publication
(1 reference statement)
2
91
0
8
Order By: Relevance
“…A hyperechoic comet-tail artifact secondary to reverberations inside the dense echogenic foreign body was visualized in three cases (Figs. 2 and 3) [3,4]. In seven cases a surrounding hypoechoic mass ranging from 1 .2 to 3 cm in diameter correlated well with inflammatory changes found at surgery (Fig.…”
Section: Eight Foreignsupporting
confidence: 63%
“…A hyperechoic comet-tail artifact secondary to reverberations inside the dense echogenic foreign body was visualized in three cases (Figs. 2 and 3) [3,4]. In seven cases a surrounding hypoechoic mass ranging from 1 .2 to 3 cm in diameter correlated well with inflammatory changes found at surgery (Fig.…”
Section: Eight Foreignsupporting
confidence: 63%
“…These narrow repetition artifacts are known as ring-down artifacts 7,8 or comet-tail artifacts. 9,10 In the present study, various pulmonary diseases showed ring-down artifacts on ultrasonography. When the parenchymal abnormalities seen in the right lung base were extensive (especially in the patients of groups 2 and 3), the ring-down artifacts were obtained along the entire diaphragm.…”
supporting
confidence: 49%
“…Comet tail artifacts occur when there is a marked difference in acoustic impedances between an object and its surround (Ziskin et al 1982). The denser composition of glass and metal created multiple internal reflections creating a series of echoes expressed as multiple small bands characterized as comet tails (Thickman et al 1983).…”
Section: Discussionmentioning
confidence: 99%